Examining the relationship between internet addiction, psychological resilience, social isolation and organisational citizenship behaviour - Selman Cutuk; Fikret Soyer (ROL Spor Bilimleri Dergisi)
The purpose of this study is to examine the relationships between internet addiction, social isolation, psychological resilience and organisational citizenship behaviour in physical education teachers. For this purpose, a hypothetical model was developed based on the relevant literature. The research was conducted with 840 physical education teachers working in schools affiliated to the Ministry of National Education between 2020-2021 academic years.  Young Internet Addiction Scale, Nottingham Health Profile (NSP), Psychological Resilience Scale for Adults, Organisational Citizenship Behaviour Scale and Personal Information Form were used in the study.  Descriptive statistics and structural equation modelling (SEM) were used to analyse the data. The significance level was determined as 0.05. According to the results obtained from the analyses, the proposed hypothetical model was confirmed. Accordingly, internet addiction positively affects social isolation. On the other hand, internet addiction affects psychological resilience negatively. The effect of social isolation on psychological resilience is negative. Psychological resilience has a positive effect on organisational citizenship behaviour. In the proposed model, it was found that there are direct effects between internet addiction, social isolation, psychological resilience and organisational citizenship behaviour, but there are no indirect effects.